Results of monitoring of local glaciers at Terra Nova Bay (Victoria Land, Antarctica) - BARONI, CARLO; FREZZOTTI M; MENEGHEL M; OROMBELLI G; SMIRAGLIA G; VITTUARI L. (1995)
Two small local glaciers have been studied in the coastal area of Terra Nova Bay. The first, Strandline Glacier, is located on the Northern Foothills at the southern margin of Gerlache Inlet (740 42' S, 164002' E), and the second is an unnamed glacier at Tarn Flat, near Mt. Gerlache (750 00' S, 162030' E). Both glaciers consist entirely of cold ice and are mainly fed by wind-blown snow, while year-round ablation is also controlled by wind. Mass balance measurements of Strandline Glacier (0.47 km") show a small deficit: annual totals range from about +52,000 m"yr -1 to about -48,000 m"yr -1 w.e. The mean flow rate varied from 0.7 to 2.3 m yr -1. During the period from 1956 to 1993 the front was stable. Comparison of Digital Terrain Models (DTM) of the glacier surface in 1956 and 1985 shows surface lowering, indicating a total ice volume reduction of 0.7 x 10 6m3(24 xlG'm"yr -1) with a mean annual specific balance of -40 mm yr -1 w.e. The "Tarn Flat" Glacier (0.33 km 2)monitored since 1989/90, showed a total net balance of -33,000 m 3yr -1 w.e. (specific mass balance: -100 mm yr -1 w.e.). The highest flow rate was 2.3 m yr -1.